Abschlussbericht zum KALMAR A Leitantrag : KALMAR - Kurile-Kamchatka and Aleutean marginal sea island arc system: geodynamic and climate interaction in space and time - Unknown (Technische Informationsbibliothek u. Universitätsbibliothek, 2010)
Kurile-Kamchatka and Aleutean marginal sea island arc systems: geodynamic and climate interaction in space and time (KALMAR) ...